Palladium‐Catalysed Carbo‐ and Hydroamination of Allenyl Ethers and Aminoallenes: Available Entry to Nitrogen‐Containing Benzo‐Fused Rings. Issue 26 (17th August 2016) - Gazzola, Silvia; Beccalli, Egle M.; Bernasconi, Alice; Borelli, Tea; Broggini, Gianluigi; Mazza, Alberto
Abstract : The Pd‐catalysed reactions of allenyl ethers and allenylamines derived from commercially available o ‐aminophenols and o ‐nitroaniline have been studied. Using a wide variety of aryl‐ and heteroaryl halides, carboamination of the allenes led to sequential C–C and C–N bond formation. Both carbo‐ and hydroamination processes resulted in the formation of nitrogen‐containing benzo‐fused rings. In the case of aminoallenes arising from o ‐phenylenediamine, the regioselectivity of the cyclization step was strongly dependent on the protecting group tethered to the nitrogen atoms, allowing the formation of five‐ and seven‐membered rings. Abstract : Carbo‐ and hydroamination reactions of allenyl ethers and aminoallenes have been developed to obtain 2‐styryl‐ and 2‐vinyldihydrobenzoxazoles and ‐dihydrobenzimidazoles.